Synbiotic-driven modulation of the gut microbiota and metabolic functions related to obesity: insights from a human gastrointestinal model - Mok, Kevin; Tomtong, Putsawee; Ogawa, Takuma; Nagai, Kenshiro; Torrungruang, Pitchsupang; Charoensiddhi, Suvimol; Nakayama, Jiro; Wanikorn, Bandhita; Nitisinprasert, Sunee; Vongsangnak, Wanwipa; Nakphaichit, Massalin (BMC microbiology, 2025)
Synbiotic interventions have gained increasing attention for modulating gut microbiota and metabolic functions in obesity-related disorders. This study evaluated the effects of Limosilactobacillus reuteri KUB-AC5 (10⁸ CFU) and Wolffia globosa powder (6 g/day) using an in vitro continuous human gastrointestinal model. Fecal samples from obese donors were used to simulate the ascending and descending colon, with microbial viability, diversity, and metabolite production assessed over 14 days via culture-dependent and culture-independent methods. Synbiotic supplementation increased anaerobic bacterial counts by 2.6 log CFU/mL in the ascending colon and 2.2 log CFU/mL in the descending colon, with notable increases in lactic acid bacteria and reductions in Enterobacteriaceae. Metagenomic analysis revealed an increasing trend in microbial diversity and evenness after 7 days of treatment, though the changes were not statistically significant. PERMANOVA analysis confirmed significant shift in microbial community composition between stabilization, treatment, and washout periods (p < 0.05). Additionally, butyrate levels significantly increased (p < 0.05), while p-cresol, a deleterious metabolite, significantly decreased (p < 0.05). Bile acid composition was modulated, with increased tertiary bile acid 3-oxo-LCA and enhanced bile acid deconjugation, suggesting improved lipid metabolism and potential weight management benefits. These findings highlight the potential of synbiotic supplementation to enhance beneficial bacterial populations, improve microbial diversity, and support metabolic health in obesity management.